Private healthcare quality : applying a SERVQUAL model - Muhammad Mohsin, Butt; Ernest Cyril, de Run (Emerald Group Publishing Limited, 2010)
Results indicate a moderate negative quality gap for overall Malaysian private healthcare service quality. Results also indicate a moderate negative quality gap on each service quality scale dimension. However, scale development analysis yielded excellent results, which can be used in wider healthcare policy and practice.